DIVERGING PERSPECTIVES ON ENERGY PERFORMANCE GAPS IN GREEN BUILDINGS: AN EMPIRICAL STUDY OF INDUSTRY EXPERTS - Shaardan, Nur ‘Atiqah; Myeda, Nik Elyna; Zaid , Suzaini Mohamed (Journal of Surveying, Construction and Property, 2025)
Green buildings continue to underperform in actual energy use compared to predicted values, revealing persistent energy performance gaps. This study explores the differing perspectives of industry experts on the root causes of and its strategies in this issue. A structured survey was administered to 278 respondents and analyzed using Relative Importance Index (RII) and Kendall’s W to measure agreement across three expert subgroups: those uninvolved in green buildings, involved but uncertified, and certified facilitators. Results reveal consistent rankings for major factors such as occupant awareness and leadership commitment but also highlight nuanced differences in how subgroups perceive organisational versus technical contributions. This study informs tailored energy management interventions and highlights the value of expert diversity in shaping sustainable building strategies.